Picturing England the photographic collections of Historic England - Evans, Mike 19xx-; Winter, Gary; Woodward, Anne (Historic England, 2015)
Photographers have taken pictures of England's buildings and landscapes since the invention of the medium, making images of the traces of past societies as well as photographing the new buildings around them. They have done so for man reasons: to capture the picturesque; to make a living or a souvenir; to promote or to condemn; to record what is disappearing or to reveal what is normally hidden. The formats and types of photograph they have used have been, over time, just as various, from the rare and special image, such as the first calotype, to the ubiquitous digital photograph. Collectively these photographers, both famous and anonymous, have changed the way we see and understand our environment.0This book features over 297 striking photographs from the Historic England Archive, an unparalleled collection of 8 million images on England's buildings and landscapes. Viewed collectively, its photographic collections re cord the changing face of England from the beginning of photography to the present day. They form a remarkable national asset, a huge memory bank that helps us understand and interpret the past, informs the present and assists with future management and appreciation of the historic environment
Includes bibliographical references (p. 327-329) and index
Keywords: Historic Buildings and Monuments Commission for England; Geschichte 1800-1900; Geschichte 1850-2015; Photography / Great Britain / History / 19th century; Geschichte; Fotografie; Great Britain / History / 19th century / Pictorial works; Großbritannien; England; Katalog